The Al-Mujadalah Approach In Preventing Sexual Orientation Deviations Among Students In Islamic Boarding Schools - Saripaini, Saripaini; Anikoh, Indifatul (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Pontianak, 2024)
Sexual orientation deviation is a problem that undermines moral values, ethics, noble principles, and goes against the principles of any religion. Therefore, the existence of individuals with same-sex preferences is not widely accepted by a significant portion of the Indonesian society. However, the phenomenon of sexual orientation deviation has spread everywhere, including in dormitories, correctional institutions (prisons), and even within the environment of Islamic boarding schools. The fact that must be acknowledged is that religious-based educational institutions or Islamic boarding schools, where the functions of education and religion converge into a single environment, can potentially trigger students to experience sexual orientation deviations. This issue should not be taken lightly, let alone ignored. Therefore, students require assistance with a suitable, structured method that has the capacity to prevent sexual deviations from occurring. This research has the objectives to elucidate how the al-Mujadalah approach can prevent deviations in sexual orientation among students in Islamic boarding schools. This research adopts a qualitative research design in the form of a literature review. Data analysis results were verified through focus group discussions. The research outcomes indicate that (1) factors contributing to the occurrence of homosexual behavior in Islamic boarding schools are triggered by the environment, namely, the restriction of interaction between male and female students, the situations surrounding the students that lead them to engage in various activities together, such as researching, eating, sleeping, storytelling, and even bathing. These habits are passed down by senior students who have been influenced. (2) The al-Mujadalah approach can be understood as an exchange of ideas through evidence-based arguments or reasoning between counselors and counselees, aimed at resolving the issues faced by the counselees. Guidance provided to adolescent students should be presented with effective strategies and high-quality argumentation patterns, including claims, grounds, warrants, backing, modal qualifiers, and rebuttals.Penyimpangan orientasi seksual merupakan masalah yang merongrong nilai-nilai moral, etika, prinsip luhur, dan bertentangan dengan prinsip-prinsip agama mana pun. Oleh karena itu, keberadaan individu dengan preferensi sesama jenis tidak diterima secara luas oleh sebagian besar masyarakat Indonesia. Namun, fenomena penyimpangan orientasi seksual telah menyebar di berbagai tempat, termasuk asrama, lembaga pemasyarakatan (penjara), bahkan di lingkungan pesantren. Fakta yang harus diakui adalah bahwa lembaga pendidikan berbasis agama atau pesantren, di mana fungsi pendidikan dan agama berpadu dalam satu lingkungan, berpotensi memicu santri mengalami penyimpangan orientasi seksual. Masalah ini tidak boleh dianggap remeh, apalagi diabaikan. Oleh karena itu, santri memerlukan pendampingan dengan metode yang sesuai dan terstruktur untuk mencegah terjadinya penyimpangan seksual. Penelitian ini bertujuan untuk menjelaskan bagaimana pendekatan al-Mujadalah dapat mencegah penyimpangan orientasi seksual di kalangan santri pesantren. Penelitian ini menggunakan desain penelitian kualitatif berbentuk kajian pustaka. Hasil analisis data diverifikasi melalui diskusi kelompok terfokus (focus group discussion). Hasil penelitian menunjukkan bahwa: (1) Faktor-faktor penyebab perilaku homoseksual di pesantren dipicu oleh lingkungan, yaitu pembatasan interaksi antara santri laki-laki dan perempuan, serta situasi di mana santri terlibat dalam berbagai aktivitas bersama, seperti belajar, makan, tidur, bercerita, hingga mandi. Kebiasaan ini diturunkan oleh santri senior yang telah terpengaruh. (2) Pendekatan al-Mujadalah dipahami sebagai pertukaran ide melalui argumen atau penalaran berbasis bukti antara konselor dan konseli, yang bertujuan untuk menyelesaikan masalah yang dihadapi konseli. Bimbingan yang diberikan kepada santri remaja harus disajikan dengan strategi efektif dan pola argumentasi berkualitas tinggi, termasuk klaim, landasan, jaminan, dukungan, penguat modal, dan sanggahan.